Does practicing physical activity influence functional capacity, pain intensity, and trunk extensor strength in individuals with chronic low back pain? Physical activity and functional capacityin individuals with pain - tavella Navega, Marcelo; Meca Pontes Ferreira, Renan (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Low back pain (LBP) is characterized as pain or discomfort located in the region below the rib cage and above the upper gluteal line. Some factors, such as a low level of physical activity or a sedentary lifestyle and poor posture during work activities, contribute to the chronification of pain. Objective: To investigate whether physical activity influences functional capacity, pain intensity and trunk extensor strength in individuals with chronic LBP. Methods: The sample was composed of 30 adult individuals, aged between 18 and 30 years, of both genders. They were divided into two groups, sedentary (SG, n=17) and active people (AG, n=13). The IPAq was used to classify the participants between sedentary and active people. Afterwards, the Roland Morris Disability and the SF-36 quality of life questionnaires were applied. Pain intensity was obtained by the Numerical Pain Scale (NDS). After that, the Sitting and Reaching Test (SCT) and the evaluation of the strength of the trunk extensor muscles were performed. At the end of the evaluations, a lumbar overload protocol was performed. After five minutes, pain intensity, flexibility, and muscle strength were reassessed. For data interpretation, a significance level of p < 0.05 was adopted. Results: After the lumbar overload protocol, the GS showed an increase in the flexibility of the posterior chain in the SRT and there was a increase in pain for both groups. Conclusion: individuals with chronic LBP, with similar levels of Quality of Life, pain intensity and disability, regardless of being active or sedentary, do not differ in pain perception, flexibility and ability to generate trunk extension force after being submitted to a lumbar overload protocol. Furthermore, the lumbar overload protocol was efficient in generating increased pain in both groups.